2019
DOI: 10.1103/physrevlett.123.143201
|View full text |Cite
|
Sign up to set email alerts
|

Light Induced Inverse-Square Law Interactions between Nanoparticles: “Mock Gravity” at the Nanoscale

Abstract: The interaction forces between identical resonant molecules or nanoparticles, optically induced by a quasimonochromatic isotropic random light field, are theoretically analyzed. In general, the interaction force exhibits a far-field oscillatory behavior at separation distances larger than the light wavelength. However, we show that the oscillations disappear when the frequency of the random field is tuned to an absorption Fröhlich resonance, at which the real part of the particle's electric polarizability is z… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The light-induced interaction force between two identical, absorbing nanoparticles separated along the z axis in a homogeneous, isotropic, random electromagnetic field is given in refs and . Note that this field is random in space and in time, with fixed frequency and amplitude.…”
Section: Nonreciprocal Isotropic Optical Forcesmentioning
confidence: 99%
See 1 more Smart Citation
“…The light-induced interaction force between two identical, absorbing nanoparticles separated along the z axis in a homogeneous, isotropic, random electromagnetic field is given in refs and . Note that this field is random in space and in time, with fixed frequency and amplitude.…”
Section: Nonreciprocal Isotropic Optical Forcesmentioning
confidence: 99%
“…However, optical forces between two particles in a dimer may be also induced in an isotropic radiation bath consisting of fluctuating electromagnetic waves with random orientations and polarizations. These optical interactions between nanoparticles in isotropic fluctuating fields have been investigated over the last few years. , When they were calculated with the consideration of absorbing particles, they led to unexpected features, such as near- and far-range inverse-squared interactions and the fulfillment of Kepler’s laws . In order to use this system to induce active motion, we must determine the asymmetry conditions needed to obtain a nonreciprocal force among the particles forming the dimer.…”
mentioning
confidence: 99%
“…Such a "gravitational-like" interaction leads to stable Bose-Einstein condensates that are self-bound (without an additional trap) with very interesting properties. Light-induced dipole-dipole interactions were intensively studied in experiments [110] and theory [111], leading to more recent observations of long-range one-dimensional gravitational-like interactions in a neutral atomic cold gas [112], or light induced inverse-square law interactions between nanoparticles [113]. The drawback of this approach is that light induced dipole interactions contain not only a conservative part, but a dissipative part too.…”
Section: B Utracold Atomsmentioning
confidence: 99%
“…He also showed that forces acting on particle dimers in an optical lattice may bring them to a halted diffusion regime . In his pursuit of novel phenomena, he proposed schemes in which unconventional gravity-like forces could be established between dielectric particles . Still in photonics, he tackled the ever challenging area of disorder photonics and chartered the problem by contributing a phase diagram in correlation-frequency space and determining the boundaries of the Anderson localization regime.…”
mentioning
confidence: 99%
“…2 In his pursuit of novel phenomena, he proposed schemes in which unconventional gravity-like forces could be established between dielectric particles. 3 Still in photonics, he tackled the ever challenging area of disorder photonics and chartered the problem by contributing a phase diagram in correlation-frequency space 4 and determining the boundaries of the Anderson localization regime. He further realized that Mie resonances of magnetic character can be isolated in small dielectric particles of high refractive index to reveal a magnetic response in dielectric materials at optical frequencies, 5 based on which he proposed the control of emitted radiation with ingenious combinations of magnetic and electric response.…”
mentioning
confidence: 99%